2011
DOI: 10.1097/iae.0b013e3182069a8f
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and Outcome of Patients With Punctate Inner Choroidopathy at a Tertiary Referral Center

Abstract: Of punctate inner choroidopathy patients in this series, 75% had CNV, and more than 30% developed multiple neovascular membranes. With treatment, all patients with follow-up of ≥ 3 years had >20/40 vision in at least 1 eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 9 publications
2
17
0
Order By: Relevance
“…PIC commonly occurs in young, healthy individuals of Caucasian origin [1,12,13]. Similar to our data (mean age 35 years), other authors reported a mean age around 30-41 years [1,9,13,15]. Consistent with other reports [12,25,27], our patients were predominantly Caucasian (100%), myopic (75%) and female (69%).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…PIC commonly occurs in young, healthy individuals of Caucasian origin [1,12,13]. Similar to our data (mean age 35 years), other authors reported a mean age around 30-41 years [1,9,13,15]. Consistent with other reports [12,25,27], our patients were predominantly Caucasian (100%), myopic (75%) and female (69%).…”
Section: Discussionsupporting
confidence: 94%
“…Here, we present a monocentric retrospective data analysis of 16 patients with CNV secondary to PIC with a mean follow-up of 15 months. PIC commonly occurs in young, healthy individuals of Caucasian origin [1,12,13]. Similar to our data (mean age 35 years), other authors reported a mean age around 30-41 years [1,9,13,15].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations